Modelling the impact of climate change risk on supply chain performance - ER, MERVE (TAYLOR & FRANCIS LTD, 2021)
Climate change is among the top global risks due to its growing adverse impact on businesses. However, few empirical studies address this imminent risk from a supply chain perspective. Due to a lack of established approaches for capturing complex interaction between climate change risk and supply chain performance, a three-phase mixed methodology approach was attempted. A cognitive map first captured the inter-relationships based on a mental model established by a group of experts. Later, a survey gathered from industry practitioners assessing causal relationships identified key climate change factors and most influenced supply chain performance dimensions. Finally, a system dynamics model supported by multiple case scenarios assessed the implications of climate change on supply chain performance. The results indicated a significant reduction in the availability of natural resources/raw material and capacity, leading to increase in stock-outs, inventory costs and bottlenecks disrupting procurement, manufacturing and logistics functions. Supply chain performance captured through efficiency and effectiveness shows a negative trend with increasing climate change consequences. The systems approach followed in this paper contributes by providing a quantitative model for assessing the impact of climate change risk on supply chain performance.
Keywords: Supply chain performance; climate change; performance measurement; climate risk; uncertainty; systems theory